2013
DOI: 10.1080/02705060.2012.753121
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate communities of groundwater-dependent refugia with varying hydrology and riparian cover during a supraseasonal drought

Abstract: Extreme disturbances eliminate aquatic biota and alter community structure and function. During a supraseasonal drought in north-central Texas in the summer and fall 2006, macroinvertebrate communities from persistent groundwater-dependent macrohabitats of varying hydrology and riparian shading were investigated to study their role as invertebrate refugia, and to characterize the taxonomic and functional community structure of benthic assemblages. Ash Creek was the only stream with surface flow within a 35-km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The non-perennial stream shifted towards aquatic macroinverterbate communities consisting more of generalist, opportunistic species driven by flow conditions. Macroinvertebrate response to changing environmental conditions thus becomes predictable, where reduced or no flows causes taxa less resilient to change to perish and the resumption of flows after no-flow periods allows macroinvertebrate communities to slowly re-establish in the biotopes (Burt & Kennedy 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The non-perennial stream shifted towards aquatic macroinverterbate communities consisting more of generalist, opportunistic species driven by flow conditions. Macroinvertebrate response to changing environmental conditions thus becomes predictable, where reduced or no flows causes taxa less resilient to change to perish and the resumption of flows after no-flow periods allows macroinvertebrate communities to slowly re-establish in the biotopes (Burt & Kennedy 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Functioning riparian areas enhance aquatic species resilience as riparian plants can stabilize banks and provide organic matter to aquatic species . Springs, seeps, and groundwater connections in some Great Plains streams can, on a local level, mitigate drier conditions (Burk and Kennedy 2013;Dodds et al 2004).…”
Section: Factors That Enhance Resilience To Nonclimate Stressorsmentioning
confidence: 99%
“…Although crayfish and many other benthic macroinvertebrates survive drought and flooding by adapting their life history behaviors and movement, Fritz and Dodds (2004) reported that recolonization from unaffected areas was a primary means of recovery in northeastern Kansas. Burk and Kennedy (2013) noted the importance of groundwater-dependent refugia for macroinvertebrate communities in the recent drought in Texas. Recovery of communities under future warming and drought will depend on the ability of species to adapt, and also the availability of habitat along the streams that species may recolonize after drying periods.…”
Section: Benthic Macroinvertebrate Speciesmentioning
confidence: 99%
See 2 more Smart Citations